Genetic control of quantitative and qualitative traits of Calycophyllum spruceanum in the Peruvian Amazon - Chávez, Jorge Manuel Revilla [UNESP]; Sebbenn, Alexandre [UNESP] (FapUNIFESP (SciELO), 2024)
Families of 38 month-old Calycophyllum spruceanum planted at three locations in the Peruvian Amazon were analyzed for breeding purpose. Significant differences were detected among families, sites and combined sites for the traits trunk diameter (D), height (H), number of nodes (NN), number of branches (NB) and survival rate (SUR), except for NN at site 2 and SUR at site 3 and combined sites. The correlation of the genotype-environment interaction was simple for D, H, NN, and SUR (0.77-0.89). Heritability was generally highest for D, H, NN, and NB (0.12-0.7), and the genotypic coefficient of variation ranged from 8.6-27.4%. Genetic correlations between these traits within and among sites ranged from 0.35-1.0. The selection of 75 trees from different families, within blocks and locations, suggested the possibility of genetic gains (6.1-29.8%) for D, H, NN, and NB, and that the remaining effective population size can be exploited in future selection cycles.
Keywords: Genetic correlations; genetic variation; heritability; progeny test; tree breeding